The willingness and attitudes of medical students regarding organ donation and transplantation: a cross-sectional study from Turkey - Sengul,Seniz (2022)
SUMMARY OBJECTIVE: Positive attitudes and motivation on the part of medical students concerning organ donation and transplantation are very important in terms of the growing need for these. This study aimed to evaluate the willingness and attitudes of medical students toward organ donation and transplantation. METHODS: This cross-sectional study was performed at a state university in Turkey in February–March 2020. The questionnaire investigated sociodemographic characteristics and willingness toward organ donation and transplantation and contained the Organ Donation Attitude Scale. RESULTS: A total of 309 medical students participated, of which 71.2% were willing to donate their organs. Medical students’ willingness to donate organs increased depending on gender, academic year, receipt of education on the subject, discussing donation with family and friends, possession of an organ donation card, knowledge of the organ donation system, and willingness to receive organ donation if necessary. Positive attitudes toward organ donation increased after discussing the subject with family and friends, possessing an organ donation card, and knowing the path to be followed for organ donation. CONCLUSION: Medical students exhibited high willingness and positive attitudes regarding organ donation and transplantation. However, education on the subject of organ donation and transplantation is needed.